Economic Theory and Working Class Poverty towards a Reformulation - Swinton, David H. (American Economic Review, 1987)
Historically, poverty rates for minority individuals and families have been substantially higher than poverty rates for nonminorities. Moreover, after several decades of decline, poverty rates have been increasing for the last decade for both minority and nonminority individuals. The traditional gap between minority and nonminority poverty rates arises primarily within the working class and is largely attributable to differences in minority and nonminority labor market earnings. It also seems clear that much of the recent increase in poverty among the working class is a direct result of increasing employment problems and declining real wage rates. Minority individuals, especially minority males, have been particularly hard hit by these recent labor market trends. Explanations of poverty and racial differentials in poverty rates among the working class derived from conventional economic theory have correctly emphasized limited earnings in the labor market as the primary determinant of individual poverty and differences in group poverty rates. However, it is the contention of this paper that the conventional explanation of how labor markets generate poverty and poverty rate differentials among the working class is seriously limited and flawed, and thus provides a poor basis for generating good antipoverty policy advice. I propose an alternative view of how labor markets work to generate poverty that provides a richer basis for generating good policy advice. I. Conventional Explanations for Working Class Poverty